Efeitos da Pandemia da Covid-19 na dinâmica do turismo de segundas residências em Armação dos Búzios/RJ e Bertioga/SP: transformações e permanências - Luciano Muniz Abreu; Isabella Maria Beil; Daniel De Renzo Barretti (Confins)
This work analyzes the main transformations and permanencies related to the phenomenon of second-home tourism in the Sars-Cov-2 pandemic context in Brazil, understood here as an accelerating element of processes that were already being experienced by the phenomenon before the sanitary crisis. It starts from the understanding that the so-called secondary homes, their spatialization and the dynamics linked to them are expressed through an imbricated relationship of socio-spatial factors and contradictions. In this sense, despite the occurrence of transformations regarding the use of secondary homes, it appears that this practice continues to converge to an increasingly greater possibility of financial gains and to greater inequality and socio-spatial segregation. The findings have shown that the pandemic has played a relevant role in accelerating these processes. Two important coastal tourist resorts, where there is a strong incidence of secondary homes, Bertioga/SP and Armação dos Búzios/RJ, which, due to their proximity to the two main national metropolises, São Paulo and Rio de Janeiro, respectively, maintain with these strong relations concerning tourism. The qualitative analyses are complemented by quantitative data related to the phenomenon under study, supporting the inferences and interpretations of the findings.